The Effects of Haze on the Spectral and Statistical Properties of Land Cover Classification - Asmala, A.; Shaun, Quegan (HIKARI LTD, 2014)

(untitled)
Haze occurs almost every year in Malaysia and is caused by smoke which originates from forest fire in Indonesia. It causes visibility to drop, therefore affecting the data acquired for this area using optical sensor such as that on board Landsat satellite. The effects of haze on the data can be observed from the spectral and statistical properties of land cover classification. The work presented in this thesis is meant to analyse the statistical properties of land cover classification of hazy dataset. Maximum Likelihood (ML) was found to be a preferable classification scheme in which the effects of haze can be investigated. The study made use of hazy dataset that were simulated based on real haze spectral and statistical properties. By investigating these dataset, the spectral and statistical properties of the land classes can be systematically analysed, in which showing that haze modifies the class spectral signatures and statistical properties, consequently causing the data quality to decline.